2009
DOI: 10.1105/tpc.108.064451
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis LTPG Is a Glycosylphosphatidylinositol-Anchored Lipid Transfer Protein Required for Export of Lipids to the Plant Surface  

Abstract: Plant epidermal cells dedicate more than half of their lipid metabolism to the synthesis of cuticular lipids, which seal and protect the plant shoot. The cuticle is made up of a cutin polymer and waxes, diverse hydrophobic compounds including very-long-chain fatty acids and their derivatives. How such hydrophobic compounds are exported to the cuticle, especially through the hydrophilic plant cell wall, is not known. By performing a reverse genetic screen, we have identified LTPG, a glycosylphosphatidylinositol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
273
1
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 322 publications
(295 citation statements)
references
References 41 publications
7
273
1
7
Order By: Relevance
“…Recently reported evidence on the possible multifunctionality of nsLTPs in plant growth processes [6][7][8] and open questions on the antigenic interactions of plant nsLTPs in alimentary allergies (particularly peach nsLTP), [58][59][60][61] pose the need to deepen our understanding on their lipid binding properties. In addition, we aimed to gain insight into general protein-ligand interactions by providing quantitative information on the lipid binding abilities of these small proteins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently reported evidence on the possible multifunctionality of nsLTPs in plant growth processes [6][7][8] and open questions on the antigenic interactions of plant nsLTPs in alimentary allergies (particularly peach nsLTP), [58][59][60][61] pose the need to deepen our understanding on their lipid binding properties. In addition, we aimed to gain insight into general protein-ligand interactions by providing quantitative information on the lipid binding abilities of these small proteins.…”
Section: Discussionmentioning
confidence: 99%
“…This observation, which has been until now mostly ignored, is the major issue addressed in this work. Recent reports on new possible roles of LTPs [7,8] have highlighted the presence of these small proteins in extracellular matrix (ECM) regions where disparate molecules with negatively charged moieties are abundant. [8] NsLTPs have net positive charge and generate electrostatic potentials predominantly positive (see below), which must be related with their distribution in the ECM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anchor of GAPs can be removed by specific phospholipases, thereby releasing the protein from the membrane (Griffith and Ryan, 1999). Genomic analysis has identified 245 and 294 GAPs in Arabidopsis and rice, respectively (Eisenhaber et al, 2003), and the reported functions of Arabidopsis GAPs are of great diversity, including cell expansion (COBRA, Schindelman et al, 2001;Roudier et al, 2005), root elongation under salt stress (SOS5/FLA4, Shi et al, 2003), cuticular lipid export (LTPG, Debono et al, 2009), callose deposition and plant cell-to-cell communication (PDCB, Simpson et al, 2009), vascular development (AtXYP1 and AtXYP2, Motose et al, 2004), double fertilization and early seed development (LORELEI, Capron et al, 2008;Tsukamoto et al, 2010), and disease resistance (PMR6, Vogel et al, 2002;NDR1, Coppinger et al, 2004).…”
Section: Srl1 Is a Putative Gapmentioning
confidence: 99%
“…Cutin is a polyester insoluble in organic solvents consisting mainly of fatty acid oxygenated derivatives with a chain length of 16 and 18 carbons, whereas cuticular wax is a complex mixture of very long-chain fatty acid derivatives, terpenoids, and phenolic components (Nawrath, 2002(Nawrath, , 2006. In plant vegetative organs, such as stem and leaf, it is believed that cuticular lipid biosynthesis occurs exclusively within epidermal cells from which lipidic molecules are transported to the organ surface by ATP binding cassette G (ABCG) transporters and lipid transport proteins (LTPs; Sieber et al, 2000;Nawrath, 2002;Pighin et al, 2004;Bird et al, 2007;Panikashvili et al, 2007;Debono et al, 2009). However, biosynthesis and transport of cuticular lipids in reproductive organs remain largely unknown.…”
mentioning
confidence: 99%